Determination of Aluminum, Copper and Lead in Aleppo Company of Cable Industry (Syria) Using Industrial TSP, PM10 and Chemical Trap Methods - AZIZ RAMADAN, ABDUL; MANDIL, HASNA; HASAN ISMAIL, MAHMOUD (Asian Journal of Chemistry, 2010)
Determination of Al, Cu and Pb in Aleppo Company of cable industry (Syria) using total suspended particles (TSP) and PM10 of aerodynamics particle sizes larger 0.3 μm and chemical trap (CT) for total elements in air were studied. Al, Cu and Pb contents in working atmos-phere with TSP, PM10 and CT in different sections were measured by atomic absorption spectroscopy. The mean TSP and PM10 levels were at 805.8 to 1130.2 and 264.5 to 350.2 μg/m3, respectively. Air Al, Cu and Pb concentrations were at 2.67 to 85.2 and 0.23 to 6.55; 3.8 to 228.7 and 0.27 to 16.84; 0. 21 to 77.5 and 0.17 to 32.62 μg/m3 using TSP and PM10, respectively, (Al, Cu and Pb in TSP and PM10 were at 0.326 to 10.46 and 0.087 to 2.54 %; 0.46 to 20.24 and 0.10 to 6.58 %; 0.039 to 9.47 and 0.059 to 12.33 %, respectively). The total mean air Al, Cu and Pb pollutants using Chemical Trap (CT) were at 3.02 to 94.2, 4.1 to 242.0 and 0.28 to 152.0 μg/m3, respectively. The results showed that, the values of TSP, PM10, Al and Cu in working atmos-phere much lower than the guideline values specified by the Occupational Safety and Health Administration (OSHA), while high levels of lead were more than the recommended maximum by OSHA; due to the fact that lead acid batteries and liquid gases plant adjacent to this factory from the western side and the wind direction often from west to east